Polycomb represses a gene network controlling puberty via modulation of histone demethylase Kdm6b expression - Wright, Hollis; Aylwin, Carlos F; Toro, Carlos A; Ojeda, Sergio R; Lomniczi, Alejandro (bioRxiv, 2020)
Female puberty is subject to Polycomb Group (PcG)-dependent transcriptional repression. Kiss1, a puberty-activating gene, is a key target of this silencing mechanism. Using a gain-of-function approach and a systems biology strategy we now show that EED, an essential PcG component, acts in the arcuate nucleus of the hypothalamus to alter the functional organization of a gene network involved in the stimulatory control of puberty. A central node of this network is Kdm6b, which encodes an enzyme that erases the PcG-dependent histone modification H3K27me3. Kiss1 is a first neighbor in the network; genes encoding glutamatergic receptors and potassium channels are second neighbors. By repressing Kdm6b expression, EED increases H3K27me3 abundance at these gene promoters, reducing gene expression throughout a gene network controlling puberty activation. These results indicate that Kdm6b repression is a basic mechanism used by PcG to modulate the biological output of puberty-activating gene networks. Competing Interest Statement The authors have declared no competing interest. Footnotes * https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE102471